Early Childhood Teachers’ Perceptions of Local Wisdom in Digital Literacy: A Study in the Society 5.0 Era - Indarwati; Deni Setiawan; Ali Formen; Edi Waluyo (Jurnal Pendidikan Anak Usia Dini Undiksha, 2026)
The rapid development of digital technology in the Society 5.0 era has created both challenges and opportunities in early childhood education, particularly in enhancing children’s participation through the integration of digital literacy and culturally responsive pedagogy. This study aims to analyze the influence of digital device usage and institutional quality on children’s participation in early childhood learning. The research employed a quantitative approach with a correlational design. The participants consisted of 100 early childhood education teachers selected through simple random sampling based on the Slovin formula. Data were collected using a Likert-scale questionnaire that had met validity and reliability requirements. Data analysis was conducted using Pearson correlation and multiple linear regression with the assistance of SPSS version 30. The findings revealed that digital device usage had a positive and significant correlation with children’s participation (r = 0.53; p < 0.01), while institutional quality also demonstrated a positive relationship with a lower correlation level (r = 0.32; p < 0.05). Regression analysis further indicated that digital device usage had a stronger predictive effect (β = 0.47; p < 0.01) than institutional quality (β = 0.21; p < 0.05). These findings confirm that the optimization of digital device usage plays an important role in improving children’s participation in early childhood learning. This study provides practical implications for strengthening teachers’ digital literacy and enhancing culturally based pedagogy in digital learning environments.